The Effectiveness of Group Schema Therapy on Metacognitive Beliefs and Body Image Concern in Women Seeking Rhinoplasty - Hosseini , Iman; Bahrami, Bita; Bahrainian , Seyed Abdolmajid (Psychology of Woman Journal, 2025)
Objective: The present study aimed to determine the effectiveness of group schema therapy on metacognitive beliefs and body image concern in women seeking rhinoplasty.Methods and Materials: This study employed a quasi-experimental design with a pretest-posttest and a control group. The statistical population included all women seeking cosmetic nose surgery in Tehran in 2020, from which 44 individuals were selected using purposive sampling. Among them, 22 participants were randomly assigned to the experimental group and 22 to the control group. Initially, a pretest was administered to both groups. Then, the experimental group participated in Young's schema therapy sessions, which consisted of ten sessions focused on cognitive strategies, experiential techniques, the therapeutic relationship, and behavioral pattern-breaking. Following the intervention, a posttest was administered to both groups. The research instruments included the Metacognitions Questionnaire-30 (MCQ-30) and the Fisher Body Image Scale (FBIS).Findings: The data were analyzed using SPSS version 24 and the statistical method of analysis of covariance. The results indicated that schema therapy significantly improved metacognitive beliefs and reduced body image concern in participants in the experimental group compared to the control group.Conclusion: It can be concluded that schema therapy, as an effective psychotherapeutic method utilizing diverse techniques and addressing core emotional needs, can help individuals with maladaptive metacognitive beliefs and body image concerns by reducing dysfunctional symptoms and improving their quality of life.